2019
DOI: 10.1155/2019/3057929
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Renewable and Biodegradable Cellulose Nanopaper Substrates for Transparent Light-Harvesting Devices: Interaction with Humid Environment

Abstract: Cellulose nanopaper (CNP) has attracted much interest during the last decade as a new fascinating renewable and biodegradable substrate for printed electronics and solar cells. Its outstanding optical and mechanical properties make CNP the ideal substrate for the preparation of photovoltaic devices, since its high transparency and haze favour the absorption of light from the active layer of the solar cell. However, some advances need to be done in the direction of increasing CNP stability in humid environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…Adopting low-cost solar cell substrates is a feasible way to overcome this challenge. Nanopaper is considered as a promising green substrate for solar cell construction due to its excellent mechanical properties, adjustable optical properties, and low cost [ 43 ]. Hu et al reported a transparent nanopaper-based solar cells, but the photoelectric conversion efficiency was only 0.21% [ 155 ].…”
Section: Applications Of Cellulose Nanopapermentioning
confidence: 99%
“…Adopting low-cost solar cell substrates is a feasible way to overcome this challenge. Nanopaper is considered as a promising green substrate for solar cell construction due to its excellent mechanical properties, adjustable optical properties, and low cost [ 43 ]. Hu et al reported a transparent nanopaper-based solar cells, but the photoelectric conversion efficiency was only 0.21% [ 155 ].…”
Section: Applications Of Cellulose Nanopapermentioning
confidence: 99%
“…Siding the industrially oriented research, new emerging fields of application of nanocellulose include hydrogels and aerogels [ 13 , 14 ], emulsion stabilizers [ 15 ], biocatalyst immobilizers [ 16 ], biosensors [ 17 ], drug delivery systems [ 18 ], adsorbents for contaminants [ 19 , 20 ], nanocomposites for environmental remediation [ 21 ], photonic films and transparent substrates for optoelectronic devices, as well as new nanostructured electroactive materials [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, nanocellulose-based materials show great potential for industry [ 35 ], as the principles of green and blue economies demand new sources of sustainable materials in substitution of oil-derivatives, for high volume applications in sectors, such as water treatment [ 36 ], paint and coating industry, building, hygiene, and paper industry [ 37 ]. Besides, new intriguing and emerging applications concern the use of nanocellulose in hydrogels and aerogels [ 38 , 39 ], emulsion stabilizers [ 40 ], biocatalyst immobilizers [ 41 ], biosensors [ 42 ], drug delivery systems [ 43 ], adsorbents for contaminants [ 44 , 45 ], nanocomposites for environmental remediation [ 46 ], photonic films and transparent substrates for optoelectronic devices, as well as new nanostructured electroactive materials [ 47 , 48 , 49 ]. Indeed, nanocellulose can expose a large active area, is transparent, and it is harmless for human health and the environment [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%